Technology requirements for preimplantation genetic diagnosis to improve assisted reproduction outcomes. - Munné, S; Wells, D; Cohen, J (2010)
Preimplantation genetic diagnosis has been proposed as a method to improve assisted reproduction technology outcomes, but different techniques have produced conflicting results. The use of appropriate techniques may provide positive outcomes.